The support and influence of the family on the career decisions of Young Orang Asli in Selangor - Don, Abdul Ghafar; Puteh, Anuar; Abdullah, Muhamad Yusuf Marlon; Aini, Zulkefli (International Journal of Asian Social Science, 2024)
The government's development agenda is applied to all communities, especially indigenous populations, in the fields of education and the economy. In order to achieve and preserve the living well-being of indigenous communities, a development programme is provided that includes the provision of high-quality human resources, such as youths, who can improve their families' standard of living. It encompasses not just economic activities but also elements of family, education, and social development. In addition, this article aims to identify the influence and support of families such as parents in helping young natives make decisions to choose a job that can improve the well-being of the community and their families, especially in economic terms. This study is quantitative and has a survey-style design. A survey instrument that was given to 281 indigenous teens in the state of Selangor at random was used to collect the survey data. Research has shown that the majority of indigenous teens' decisions to work are influenced by and dependent on their families, particularly their parents. A contributing component to the results was the motivation to support their families' economic growth. This study suggests that, despite their poor economic and educational standards, indigenous societies have strong family relationships. Young indigenous use their family bonds as a source of motivation while making decisions about their work.